Penerapan Hipnosis Lima Jari untuk Mengatasi Gejala Psikologis pada Masyarakat setelah Bencana Banjir di Kota Surakarta - Husain, Fida; Silvitasari, Ika; Inovasi, Monica; Islamiyah, Syafrani Nurul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: The impact of floods on communities included both physical and psychological effects. The psychological impact on individuals contributed to anxiety, encompassing various environmental and health issues, such as acute stress. Floods led to psychological manifestations, including anxiety, stress, and clinical depression. Objective: The goal of this community service project was to provide five-finger hypnosis therapy to reduce the anxiety levels of flood-affected communities. Method: The three types of activity approaches included planning, carrying out, and reviewing. Twenty community members participated in this activity, which involved a lecture and Q&A session. Result: The results of the activity concluded that providing five-finger hypnosis therapy to communities affected by natural disasters effectively reduced psychological symptoms, specifically anxiety. The instructional training was conducted without any difficulties. Conclusion: Five-finger hypnosis therapy effectively reduced anxiety in disaster-affected communities. This technique is flexible and can be performed anytime and anywhere.